Case study vale Brasil the largest ore carrier in the world (2011)
Their products and services can be found in all areas of modern society and have an essential function in ensuring life quality. Three of the main products are iron ore, coal, and manganese, fundamental components in the production of steel, which is used in basic industries, transportation, construction, and thousands of everyday activities. Others like Nickel are used in stainless steel production and in electronic and medical equipment. Copper is an essential part of telecommunications. Bauxite is the raw material for producing aluminum, widely used in industries ranging from packaging to aircraft manufacturing. The agricultural sector uses potassium and phosphate to increase yielding, while kaolin is used especially in paper manufacturing in the pharmaceutical industry and in ceramics.